2020
DOI: 10.1007/s11426-020-9868-8
|View full text |Cite
|
Sign up to set email alerts
|

An A-D-A′-D-A type unfused nonfullerene acceptor for organic solar cells with approaching 14% efficiency

Abstract: In recent years, power conversion efficiency (PCE) of organic solar cells (OSCs) has made significant improvement. A large number of studies were reported to achieve high PCEs through exploring new active layer materials, especially the high efficiency fused ring acceptors (FRAs). Compared with FRAs, another type of so-called unfused-ring acceptors (UFAs), possessing some advantages such as simple synthesis and low cost, have attracted a lot of attention. Herein, a new UFA BTzO-4F, incorporating with a benzotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 23 publications
1
98
0
1
Order By: Relevance
“…Recently, Huang et al reported an efficient unfused acceptor BTzO-4F. [67] Theoretical calculations indicate double O⋅⋅⋅S and N⋅⋅⋅H noncovalent locking between the CPDT and the dialkoxybenzotriazole units. This delivers the enhanced planarity.…”
Section: Simple-structured Yet Efficient Small Molecule Nfasmentioning
confidence: 99%
“…Recently, Huang et al reported an efficient unfused acceptor BTzO-4F. [67] Theoretical calculations indicate double O⋅⋅⋅S and N⋅⋅⋅H noncovalent locking between the CPDT and the dialkoxybenzotriazole units. This delivers the enhanced planarity.…”
Section: Simple-structured Yet Efficient Small Molecule Nfasmentioning
confidence: 99%
“…基于 PBDB-T/NTTI(w/w, 1∶1, 0.5 wt% CN)的器件的 V oc 为 0.77 V, J sc 为 17.7 mA/cm 2 , FF 为 56.0%, PCE 为 7.62%. 2020 年, 黄辉等 [147] 采用非共价"构象锁"概念, 增 强分子内部的共平面性, 设计合成了含有"S•••O"构象 锁 的 非 稠 环 受 体 材 料 BTzO-4F( 图 21m). 基 于 PBDB-T/BTzO-4F(w/w, 1∶1, 0.5 wt% CN)的器件的 V oc 为 0.84 V, J sc 为 23.6 mA/cm 2 , FF 为 69.7%, PCE 为 13.80%.…”
Section: Bta 系列受体材料unclassified
“…[13] Huang and co-workers developed a benzotriazole-cored unfused-ring acceptor BTzO-4F to realize a record high PCE 13.80% for binary OSCs by taking advantage of S….O noncovalent interactions for molecular conformation locking. [14] It should be noted that bithiophene block has an inherent shortcoming for weak electron-donating ability, which restricts its space in designing simple NFAs with facilely modulated energy levels and optical absorption. In this case, pyrrole-fused ring structures have shown great potential for construction of highefficiency FREAs, [15] where the strong electron-donating characteristics of N-atoms and extra N-alkyl sidechain engineering are advantageous for regulating FREAs' energy levels, optical absorption, solubility, and aggregation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The state-ofthe-art FREAs (such as Y6 series, dithieno[3,2-b:2′,3′-d]pyrrol (DTP) fused-core based series, and M34) containing one or two fused pyrrole rings have realized PCEs over 15% in OSCs. [14][15][16] In recent years, our group have successfully explored DTP as an excellent electron-donating block to construct FREAs based on indacenobis(dithieno[3,2-b:2',3'-d]pyrrol) symmetric core and indaceno(dithieno[3,2-b:2',3'-d]pyrrol)thiophene (IPT) asymmetric core. [17][18][19][20] Compared to M34 and Y6-seriers NFAs, the pyrrole structure in DTP unit can be built with straightforward and high-yield synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%